ANALISIS KUALITAS PELAYANAN JASA KONSULTASI BISNIS DAN MANAJEMEN DENGAN METODE SERVQUAL DAN IMPORTANCE PERFORMANCE ANALYSIS - Andi Erna Mulyana; Jessica Olifia; Hada Sufriatin (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The purpose of this research is to determine the perceptions of consulting service users based on the gap between perceptions and expectations from five dimensions, which are tangibles, responsiveness, reliability, assurance and empathy. This research also aims to identify what service quality factors are considered important to the satisfaction of the users who used the business and management consultation services at a consulting company in Batam. Data were collected using questionnaires with a sample size of 43 respondents consisting of limited liability companies and commanditaire vennootschap (limited partnership). This research calculates the level of client satisfaction with a series of tests and data analysis. The method used is the Service Quality Method (Servqual Gap 5) and Importance Performance Analysis. The research obtained data from the Servqual method shows that the overall average gap per dimension is that the tangibles dimension meets client expectations with a positive gap value, meanwhile the rest, which are responsiveness, reliability, assurance and empathy have a negative gap. Then the Importance Performance Analysis calculation shows two attributes of the quality of business and management consulting services that need to be improved, which are the services provided need to pay special attention to service users and prioritize the interests of the service users